Curcumin mitigates the epithelial‐to‐mesenchymal transition in biliary epithelial cells through upregulating CD109 expression. Issue 7 (12th August 2019) - Fan, Junyu; Wang, Qian; Zhang, Zhuoya; Sun, Lingyun
Abstract: Biliary epithelial cells (BECs) can secrete bile and the epithelial‐to‐mesenchymal transition (EMT) of BECs can cause fibrosis or damage interlobular bile ducts, leading to chronic cholangiopathies, such as primary biliary cholangitis (PBC). Transforming growth factor‐β1 (TGF‐β1) is a potent inducer of the EMT while curcumin, a diarylheptanoid, can inhibit the EMT of hepatocytes in many liver diseases. However, the protection and underlying mechanisms of curcumin against the EMT of BECs have not been clarified. Herein, we show that curcumin treatment significantly mitigates the EMT of BECs in vitro and in vivo. Mechanistically, curcumin significantly attenuated the TGF‐β1‐induced Smad and Hedgehog signaling, and upregulated CD109 expression in BECs. Collectively, these findings highlighted the therapeutic potential of curcumin to counteract the EMT process in PBC.